THYROID HORMONS IN THE THERAPEUTIC PRACTICE - Reminskaya, K. I.; Martymianova, L. O. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The clinical pharmacology of thyroid hormons in the classification system of ATS is described. Clinical classification, pharmacokinetics and peculiarities of drugs of this groupare submitted. Indications for use and features of use of thyroid hormons in a therapeutic clinic are considered.The article points out the urgency of use of these drugs curing hypothyroidism (any genesis), preventing the recidivation of nodular goiter. The primary contraindications, emphases of interaction with other drugs, side effects and symptoms of overdoseare given.